In vivo pharmacodynamics of lefamulin, the first systemic pleuromutilin for human use, in a neutropenic murine thigh infection model - Wicha, Wolfgang W (J Antimicrob Chemother, 2019)
OBJECTIVES: To characterize the pharmacokinetics (PK) and pharmacodynamics (PD) of lefamulin in the neutropenic murine thigh infection model to ascertain (i) which PK/PD index best correlates with efficacy and (ii) whether the magnitude of the index that drives efficacy varies for different pathogens. METHODS: We evaluated the in vivo PK/PD of lefamulin against five Streptococcus pneumoniae and five Staphylococcus aureus strains using a neutropenic murine thigh infection model. The relationships between bacterial burden in the thigh of normal and neutropenic mice after 24 h of lefamulin treatment and various PK/PD indices were determined. RESULTS: The kinetics of the three doses was linear by AUC. Rate of killing was maximal at concentrations near the MIC; suppression of regrowth was dose dependent, with a post-antibiotic effect of 3.0–3.5 and 1.0–1.5 h against S. pneumoniae and S. aureus, respectively. The efficacy of lefamulin correlated most strongly with the AUC(0–24)/MIC ratio; coefficient of determination was 79.9% for S. pneumoniae and 78.3% for S. aureus. The magnitude of the 24 h AUC/MIC of total drug required ranged from 9.92 to 32.1 for S. pneumoniae and 40.2 to 82.5 for S. aureus, corresponding to free drug values (∼20% free fraction) of 1.98–6.42 and 8.04–16.5, respectively. CONCLUSIONS: Lefamulin, the first systemically available pleuromutilin in humans, exhibits time- and concentration-dependent killing. The presence of white blood cells had only a slight effect in enhancing the activity of the drug, indicating a leucocyte-independent effect. The identified driver of efficacy, the AUC(0–24)/MIC ratio and the ratios determined against various S. aureus and S. pneumoniae strains, will inform further non-clinical and clinical trials.